Perlindungan Hukum Dan Keamanan Wisatawan Pada Destinasi Pariwisata Di Pantai Kuta Badung - I Made Pasek Asmaradana; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Kuta Beach is a very special beach in Bali, a beach visited by foreign and local tourists, in terms of security and legal protection, tourism managers often do not care about this, in practice it is found that tourists complain about security and legal protection at Kuta Beach based on Law Number 10 of 2009 concerning Tourism related to security and legal protection based on this, the problem is formulated, namely 1) How is tourism management in terms of tourist safety at tourism destinations on Kuta Beach Badung? And 2). How is legal protection for tourists to increase a sense of comfort when visiting Kuta Beach Badung? The research method used is the type of empirical legal research with the type of legislative approach. The results of this study indicate that the Kuta Beach manager, namely the customary bendesa, has made efforts to provide legal protection and security by establishing a beach task force and cooperating with the Police in the Kuta Village Area and applying preventive and repressive laws in the Kuta Beach area, in solving problems in the Kuta Beach area using non-litigation channels.